Identification of Active Sites for Oxygen Reduction Reaction on Nitrogen- and Sulfur-Codoped Carbon Catalysts - Villemson, Karl Markus; Kaare, Kätlin; Raudsepp, Ragle; Käämbre, Tanel; Šmits, Krišjānis; Wang, Pangpang; Kuzmin, Anton V.; Šutka, Andris; Shainyan, Bagrat A.; Kruusenberg, Ivar (American Chemical Society, 2019)
Nitrogen- and sulfur-codoped carbon catalysts were prepared as electrocatalytic materials for the oxygen reduction reaction (ORR). Herein, we propose a novel and effective one-pot synthetic approach to prepare a NS-doped carbon catalyst by using the mixture of graphene oxide and multi-walled carbon nanotubes as a carbon support. Successful NS-doping of carbon and formation of the catalytically active sites were confirmed by X-ray photoelectron spectroscopy and with energy dispersion spectroscopy. The ORR activity of NS-codoped carbon was investigated by using a rotating disc electrode method. The NS-doped carbon shows superior ORR performance in alkaline media, and the electrocatalytic mechanism for the reduction of oxygen was well explained by density functional theory calculations of graphene sheets.
This research was financially supported by ERA.Net RUS Plus funding mechanism (Project HeDoCat) and by the European Regional Development Fund project TK134.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics